Cyberbullying Phenomenon of High School Students: An Exploratory Study in West Kalimantan, Indonesia - Setiawan, William Vincent; Fitrisna, Vernawati Eva; Michellianouva, Fairuz; Mayliza, Celly Septine (Bina Nusantara University, 2020)
Cyberbullying became a common occurrence among teenagers in the world today. The aim of research explored the cyberbullying experience of high school students in West Kalimantan. The conducting this research was to identify internet usage and online activities that led to cyberbullying victimization. The methods used a questionnaire collected during June 2019 from 50 students (25 male and 25 female) grades 10 to 12, and used a one-way ANOVA analysis. Significant gender differences were found it indicated that boys were more often involved in cyberbullying both as the perpetrator and the victim. Students with lower academic achievement tend to be online perpetrators than students with better academic performance. This study investigated how cyber oppression impacts both as a perspective of victimization and persecution, discussing the practice of reporting students to parents, school officials and other adults. Parental and teacher supervision as a strategy reduces student involvement in cyberbullying and generates awareness among students. The result implies that schools have an important role in teaching cybersecurity, adding cyberbullying subject in the curriculum, and sharing experiences with students.